A 1:2 co-crystal of 2,2′-dithiodibenzoic acid and benzoic acid: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The asymmetric unit of the title 1:2 co-crystal, C14H10O4S2-2C7H6O2, comprises half a molecule of dithiodibenzoic acid [systematic name: 2-[(2-carboxyphenyl)disulfanyl]benzoic acid, DTBA], as the molecule is located about a twofold axis of symmetry, and a molecule of benzoic acid (BA). The DTBA molecule is twisted about the disulﬁde bond [the C—S—S—C torsion angle is -83.19 (8)⁰] resulting in a near perpendicular relationship between the benzene rings [dihedral angle = 71.19 (4)⁰]. The carboxylic acid group is almost co-planar with the benzene ring to which it is bonded [dihedral angle = 4.82 (12)⁰]. A similar near co-planar relationship pertains for the BA molecule [dihedral angle = 3.65 (15)⁰]. Three-molecule aggregates are formed in the crystal whereby two BA molecules are connected to a DTBA molecule via hydroxyO—H...O(hydroxy) hydrogen bonds and eight-membered {...HOC=O}2 synthons. These are connected into a supramolecular layer in the ab plane through C—H...O interactions. The interactions between layers to consolidate the three-dimensional architecture are π–π stacking interactions between DTBA and BA rings [inter-centroid separation = 3.8093 (10) A ˚ ] and parallel DTBA-hydroxy-O...π(BA) contacts [O...ring centroid separation = 3.9049 (14) A ˚ ]. The importance of the speciﬁed interactions as well as other weaker contacts, e.g. π–π and C—H...S, are indicated in the analysis of the calculated Hirshfeld surface and interaction energies.